Meninjau Ulang Perbedaan Self-Disclosure pada Siswa Introversi dan Ekstroversi: Temuan Baru dari Dunia Pendidikan - Jihan Adilla; Rezki Hariko; Dina Sukma; Puji Gusri Handayani (Indonesian Counselor Association (IKI), 2025)
The phenomenon of low self-disclosure in adolescents is one of the problems that can hinder students' social relationships and emotional development at school. The current study aims to describe the level of self-disclosure in students in general and in each personality type, as well as to examine the differences in self-disclosure between students with introversion and extroversion personality types. This study uses a quantitative method with a comparative descriptive approach. The respondents were 190 students of MAN 1 Kota Bukittinggi (95 introverts and 95 extroverts) selected using a simple random sampling technique. Data were collected through the administration of an adolescent self-disclosure scale compiled based on the Likert scale model. Analysis of differences used an independent sample t-test with the help of the SPSS program. The results showed that the overall level of student self-disclosure was in the moderate category. Meanwhile, hypothesis testing showed that there was no significant difference between the self-disclosure of introversion and extroversion students (sig = 0.894 > 0.05). These findings indicate that personality type does not significantly influence self-disclosure. This research provides insights for guidance and counseling teachers in developing services that can maintain and further enhance student self-disclosure.